Stimulation of Cellular DNA Synthesis by Human Cytomegalovirus - Jeor, Stephen C. St. (1974)
Human cytomegalovirus (CMV) is able to induce cellular DNA synthesis in both permissive (human embryonic lung) and nonpermissive (Vero) cells. The induction of cell DNA synthesis was assayed by the incorporation of [methyl-(3)H]thymidine into macromolecules having the buoyant density characteristics of cell DNA. The DNA synthesis induced by CMV infection appears to represent normal semiconservative replication as opposed to repair synthesis. Both strains of CMV tested were capable of inducing cell DNA synthesis. Virus exposed to heat or UV light prior to infection lost the ability to induce DNA synthesis, indicating that a virus-coded function expressed after infection is responsible for stimulation of cell DNA synthesis.